Vocational Training in Higher Education: A Learning Centred Approach to Integrating ‘Educultures’ - Ruigrok, Jeff (SOURCE: Sheridan Institutional Repository, 2017)
The goal of this effort is to make plain any overlap between Post-Secondary Mechanical Technician Standards and Plumbing Apprenticeship Curriculum Standards. We'll investigate whether the overlap is significant enough to create a modern and updated classroom learning template. Mechanical Technician programs are generally 56 weeks in length. A Plumbing Apprenticeship is significantly longer. The essential question is: What portion of Technician Education equates to the first 100 to 200 weeks of Apprenticeship Training. If enough meaningful and actionable overlaps do exist there may be opportunities to strengthen real-world-connections to in-school lectures and labs. The two key Standards that will be investigated include: 1) Ministry of Advanced Education and Skills Development - Mechanical Techniques / Technician Program Standards. (Queens Printer for Ontario, 2010) 2) Ontario College of Trades - Levels One / Two of the Plumbing Apprenticeship Standards. (Queens Printer for Ontario, 2007) In the making of a Standards integration framework, a third -daunting- aspect must also be discussed. That is, how does the association between the Standards suit classroom stakeholders? Where primary technologies such as Plumbing are concerned, the teaching and learning environment can vary quite a lot. Among others, the differences between applied and liberal education and, rural and urban dwellers are notable, as is male verses female engagement in the trade. If a template can meet just a few of the challenges -by being classroom-usable in both Attawapiskat and Brampton- The Author deem the results of this effort a success.